Classifying the Large Vestibular Aqueduct: Morphometry to Audiometry. Issue 1 (January 2023) - Deep, Nicholas L.; Carlson, Matthew L.; Hoxworth, Joseph M.; Driscoll, Colin L. W.; Lohse, Christine M.; Lane, John I.; Ho, Mai-Lan
Abstract : Objective: Large vestibular aqueduct (LVA) is the most common inner ear dysplasia identified in patients with hearing loss. Our objective was to systematically quantify LVA morphologies and correlate imaging findings with established audiometric outcomes. Study Design: Retrospective review. Setting: Tertiary referral center. Patients: Patients with large vestibular aqueduct identified radiographically, with or without hearing loss. Intervention(s): Diagnostic only. Main Outcome Measure(s): Vestibular aqueduct (VA) width at midpoint, width at external aperture, and length were measured on cross-sectional imaging. Morphology was classified as type I (borderline), type II (tubular), or type III (funneled). Audiometric endpoints included air/bone conduction, pure tone averages, and air-bone gaps at 250 and 500 Hz. Statistical associations were evaluated using linear regression models, adjusted for age at first audiogram and sex. Results: One hundred seventeen patients (197 ears) were included, with mean age at first audiogram of 22.2 years (standard deviation, 21.7 yr). Imaging features associated with poor audiometric outcomes were increasing VA width at midpoint and external aperture, decreasing VA length, dilated extraosseous endolymphatic sac, cochleovestibular malformations, and increasing VA type (III > II > I). Conclusions: Quantitative LVA measurements and a standardized morphologic classification system aid in prediction of early audiometric endpoints.